2022
DOI: 10.1021/acs.jcim.1c01306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interactions between SARS-CoV-2 RBD and Full-Length ACE2 with Coarse-Grained Molecular Dynamics Simulations

Abstract: Compared to all-atom models, coarse-grained models enable the investigation of the dynamics of simulation systems on a much larger length scale and a longer time scale, which makes them suitable for studying macromolecular systems. Hence, in this work, we performed multiple μs-scale Martini coarse-grained molecular dynamics simulations to reveal the interaction details between SARS-CoV-2 RBD and full-length human ACE2. Besides, the key coarse-grained systems were backmapped into the corresponding all-atom syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The binding of RBD with human ACE2 has been studied in many recent studies through computational means. Although these studies have greatly contributed to our understanding of the RBD-ACE2 binding process, many details of the molecular mechanism of the binding, the process of unbinding and associated free energy diagrams, and their variations with mutation still remain open. For example, while the experimental work of ref reported that the receptor binding domains of SARS-CoV-2 and SARS-CoV-1 bind with ACE2 with similar affinities, the biomechanical force measurements and computational studies of refs and reported that SARS-CoV-2 binds with ACE2 with higher affinity than SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of RBD with human ACE2 has been studied in many recent studies through computational means. Although these studies have greatly contributed to our understanding of the RBD-ACE2 binding process, many details of the molecular mechanism of the binding, the process of unbinding and associated free energy diagrams, and their variations with mutation still remain open. For example, while the experimental work of ref reported that the receptor binding domains of SARS-CoV-2 and SARS-CoV-1 bind with ACE2 with similar affinities, the biomechanical force measurements and computational studies of refs and reported that SARS-CoV-2 binds with ACE2 with higher affinity than SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Martini (v2.2) was used to study the SARS-Cov-2 virus. By exploiting the increased time and sizes scales inherent in CGMD, the entire viral envelope was able to be simulated. These examples show the scale of simulations possible, which remain inaccessible to all-atom MD.…”
Section: Introductionmentioning
confidence: 99%
“…Amitai 54 constructed a shape-based CG model for the SARS-CoV-2 S-protein and conducted the on-rate (targeting) analysis to predict important mutation sites in the S-protein. Gu and co-workers 55 used the MARTINI force field to simulate the binding form of SARS-CoV-2 RBD with ACE2, and they found that the plier structure at both ends of the RBD-ACE2 interface would benefit the interaction between the RBD and the full-length human ACE2. Tieleman and co-workers 56 constructed the MARTINI CG models for the intact envelopes of SARS-CoVs containing multiple S-proteins.…”
Section: Introductionmentioning
confidence: 99%